The Effect of Credit Product Knowledge and Perceived Benefits on the Utilization of Inclusive Financing by MSMEs at Bank XYZ Pekanbaru - Vennie Vennie; Daniel Joel Immanuel Kairupan (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
MSMEs play a strategic role in strengthening the national economy, yet access to formal financing remains a major obstacle. Limited financial literacy and insufficient understanding of banking products have caused many MSMEs to underutilize available credit facilitiesThis study aims to analyze the effect of credit product knowledge and perceived benefits on the utilization of inclusive financing by Micro, Small, and Medium Enterprises (MSMEs) that are clients of Bank XYZ Pekanbaru. A quantitative approach with multiple linear regression analysis was employed, and data were collected through questionnaires distributed to 112 respondents representing MSME clients. The results show that credit product knowledge has a positive and significant effect on inclusive financing utilization, and perceived benefits also exert a positive and significant influence. Simultaneous testing reveals that the two independent variables together contribute 48% to variations in inclusive financing utilization, while the remaining 52% is influenced by other factors beyond the scope of this study. These findings highlight the importance of improving financial literacy and fostering positive perceptions of credit to encourage MSMEs to make greater use of formal financial services. The practical implications suggest the need for continuous financial education strategies, simplified dissemination of banking product information, and regulatory support to strengthen financial inclusion and enhance MSME business sustainability.